UZAKTAN TÜRKÇE ÖĞRETİM PROGRAMI (TSP): HAZIRLIK, UYGULAMA, SORUNLAR VE ÇÖZÜMLER. - PİLANCI, Hülya; ÇALIŞKAN, Hasan; AYDIN, Cengiz Hakan; KARADAĞ, Nejdet; SÖKER, Nurdan; SALTIK, Olcay; KİP KAYABAŞ, Buket (Electronic Turkish Studies)
Undoubtedly, the developments in informatics are the most important ones of the 20th and 21st century. Given the historical development of the methods and approaches used in foreign language teaching, it can be seen that nearly all of these methods and approaches appeared as a result of technological inventions and scientific advances. In foreign language teaching, rich learning environments that can be enhanced by the technological tools improve four language skills, which are listening, speaking, reading and writing. With distance language teaching, learners are provided eclectic, potent and learner-centered learning opportunities. Starting from 90s, with the expanded use of communication and computer webs, particularly the Internet, languagelearning sites in variety of languages have been designed. In this way, individual and distance learning opportunities in language learning have appeared. In the present study, as one of the distance language teaching program, Turkish Certificate Program (TSP), which was prepared and applied at Anadolu University, will be mentioned. The problems experienced in the program will be discussed and possible solutions will be provided. The problems experienced can be analyzed under the following headings; organizational problems, problems related to creating course content, technical problems, problems related to learning habits, problems related to teaching habits, accreditation problems, and regulation problems.